Bridging Using Tongue Twisters to Improve Pronunciation and Confidence of Young Language Learners - Musdalifah, Mayra; Widiastuty, Hesty; Deramae, Maheeda (IKIP Siliwangi, 2025)
This research, based on a community service activity, aimed to improve pronunciation skills and boost the confidence of young language learners at the elementary level using tongue twisters. The study was conducted on July 4th, 2024, at the Miracle Language Center in Narathiwat, Southern Thailand, involving 40 students. A quasi-experimental design with pre-test and post-test assessments was employed to evaluate the program's effectiveness. Participants engaged in guided sessions featuring age-appropriate tongue twisters and interactive group activities, creating a supportive environment for practicing pronunciation. The pre-test and post-test data were analyzed using a paired t-test, which revealed a statistically significant improvement in both pronunciation and confidence levels (t=4.81,p<0.05). The findings support the hypothesis that tongue twisters are an effective tool for enhancing language learning among young learners, particularly in pronunciation and self-confidence.